The Impact of Mind Mapping on Modeling Instruction in Topic of Life Organization System to Conceptual Understanding - Zainul Mustofa (SEAMEO QITEP in Science, 2022)
Mastering the basic concepts of life organization systems is one of the main goals of learning science at the junior high school level. This study has the main objective to find out how the influence of mind mapping in learning modeling instruction on the topic of life organization systems on conceptual understanding. This research is an experimental- research with a posttest-only control group design. The population of this research is the seventh-grade students of SMP Al Munawwariyyah Malang. Sample selection using a purposive sampling technique. The research subjects consisted of 30 control class students and 34 experimental class students. The research was carried out in class VII SMP Al Munawwariyyah, Malang in the academic year 2021/2022. The results showed that there was a significant difference between the experimental and control classes with a significance of <0.05 (2-tailed). The average concept understanding of the experimental class students was 66.8> 58.0 better than the average concept understanding of the control class. Based on the calculation of the effect size obtained a value of 0.64 (enough category) which indicates that mind mapping has a positive enough effect on students' understanding of concepts in modeling instruction learning. Further research is needed to explore the effectiveness of mind mapping in more detail on different topics or subjects.